Aspek Moralitas dalam Novel Anak-Anak Pangaro Karya Nun Urnoto El Banbary: Kajian Sosiologi Sastra dan Implementasinya sebagai Bahan Ajar Sastra Indonesia di SMP - Ambarwati, Resti; , Prof. Dr. Ali Imron Al Ma'ruf, M. Hum (2017)
This study aimed to (1) describe the sosiohistoryauthor Anak-anakPangaro Novel by Nun Urnoto El Banbary, (2) describe the elements that construct Anak-anakPangaro Novel by Nun Urnoto El Banbary, (3) decribe moral aspect in Anak-anakPangaroNovel by Nun Urnoto El Banbary, and (4) describe the result ofAnak-anakPangaro Novel by Nun Urnoto El Banbary. The method of this study was descriptive qualitative. The object of this study was moral aspect in Anak-anakPangaro Novel by Nun Urnoto El Banbary. The data of this study were Anak-anakPangaro Novel by Nun Urnoto El Banbary. The secondary data of this study were research paper, journal, and articles which relevant to this study. The technique of collecting data were read dan write. This study used triangulation theory to validate the data. This study used dialectica to analyze the data. The results of this study indicate that (1) background sosiohistoris Nun Urnoto El Banbary was born on 14 June in Sumenep, Madura. Born in rural surroundings away from the hustle of the city, Nun Urnoto El Banbary from children hoby writing and reading that book decided to wander into the city after graduating from high school while continuning study. (2) the structure of Anak-anakPangaro novel work Nun Urnoto El Banbary can be seen from themes and facts of the story. The theme of this novel Anak-anakPangaro work Nun Urnoto El Banbary is the struggle of a group of school children save the island. The groove is a grove going forward. The main character in this novel is UmmiSalamah. The background used in the Madura and Raja Island. (3) moral aspek in the novel divided into (a) honesty, (b) authentic values, (c) a willingness to take responsibility, (d) moral independence, (e) moral courage, (f) humality, and (g) reality and critical. (4) this novel can be implemented on learning Indonesia Languagen Junior High 7 grade semester 2 (even).